PARLIAMENTARY REPRESENTATION AND CORRUPTION IN PERU. THE CASE OF PARLIAMENTS: 2011 - 2016 - Yalle Quincho, Omar (2020)
The present study is an approximation on Parliamentary Representation and Corruptionin Peru. (2011-2016). The problem is dealt with, from some ideas regarding corruptionand significant cases of political scandals, seen in the Ethics Committee of Parliament.It addresses, from a quantitative analysis, the citizen’s perception of Lima, regardingparliamentary representation and political corruption.